2005
DOI: 10.1016/j.jasms.2005.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ion mobility spectroscopy for determining charge-solvated versus salt-bridge structures of protonated trimers

Abstract: The cross sections of five different protonated trimers consisting of two base molecules and trifluoroacetic acid were measured by using ion mobility spectrometry. The gas-phase basicities of these five base molecules span an 8-kcal/mol range. These cross sections are compared with those determined from candidate low-energy salt-bridge and charge-solvated structures identified by using molecular mechanics calculations using three different force fields: AMBER*, MMFF, and CHARMm. With AMBER*, the charge-solvate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…As an example of the last, Jarrold and coworkers (29,30) showed that the addition of a charge on the carboxyl terminus stabilizes the helical macrodipole of polyalanine peptides in the gas phase. However, balancing charge solvation and Coulomb repulsion often dominates in smaller peptides (31)(32)(33)(34). Here, we focus on bradykinin (BK) (35,36) with the sequence RPPGFSPFR and specifically on its charge state +3.…”
Section: Peptidesmentioning
confidence: 99%
“…As an example of the last, Jarrold and coworkers (29,30) showed that the addition of a charge on the carboxyl terminus stabilizes the helical macrodipole of polyalanine peptides in the gas phase. However, balancing charge solvation and Coulomb repulsion often dominates in smaller peptides (31)(32)(33)(34). Here, we focus on bradykinin (BK) (35,36) with the sequence RPPGFSPFR and specifically on its charge state +3.…”
Section: Peptidesmentioning
confidence: 99%
“…Using molecular dynamics, Bern eche et al 12 determined that residue Lys-7 located in the hydrophobic moiety of the helix forms H-bonds with the hydrophilic end of lipid chains, anchoring the chain parallel to the bilayer. [19][20][21] An example of this latter class is shown in the work of Jarrold and co-workers, who examined a series of helix forming peptides using ion mobility mass spectrometry (IM-MS). Water molecules at the membrane interface cause disruption of the a-helix at the basic C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…These can be split into two distinguishable areas: the first to preserve and understand solution phase conformations and complex topology with careful use of native electrospray ionisation which consider systems of large molecular weight, [15][16][17][18] the second to determine intrinsic molecular interactions responsible for conformations adopted in the gas phase, often the latter is concerned with small model systems. [19][20][21] An example of this latter class is shown in the work of Jarrold and co-workers, who examined a series of helix forming peptides using ion mobility mass spectrometry (IM-MS). 22 By combining both theory and experiment, they found strong evidence for preservation of helices even at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of soft ionization techniques, and then native mass spectrometry, has motivated the development of experimental strategies for the determination of the three‐dimensional structures of molecular, and especially biomolecular systems in the gas phase. A wealth of techniques have been proposed as gas‐phase structural probes, among which infrared multiphoton dissociation (IRMPD) and ion mobility spectrometry (IMS) have been the most widely used. The hierarchical structuration of biomolecules nevertheless renders the problem of structure determination particularly tricky to solve, thus justifying the combination of putatively complementary techniques.…”
Section: Introductionmentioning
confidence: 99%